1998
DOI: 10.2500/108854188778607255
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Count and Eosinophil Cationic Protein Concentration of Induced Sputum in the Diagnosis and Assessment of Airway Inflammation in Bronchial Asthma

Abstract: Measurement of eosinophil percentages and ECP concentration in induced sputum may be useful in the diagnosis and assessment of the variability of airway inflammation in bronchial asthma (BA). To evaluate the usefulness of sputum eosinophil counts and ECP concentrations in the diagnosis of BA, we measured these parameters in 68 patients with respiratory complaints. In addition, we followed-up 14 BA patients with variable airflow limitation for 45.4 +/- 10.4 days. The BA group (n = 41) showed a higher percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…reported that bronchial eosinophil recruitment and activation may occur even in mild to moderate stable asthma and that bronchial epithelium damage and airway responsiveness may be partially associated with the eosinophilic inflammatory reaction [8]. There is also much evidence that bronchial asthma is characterized by chronic recruitment of eosinophils to the airways, and eosinophils play an important role in bronchial epithelial damage in asthma by releasing cationic proteins [9–11]. Allergen exposure in atopic asthmatic patients is associated with recruitment and activation of eosinophils in the airways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that bronchial eosinophil recruitment and activation may occur even in mild to moderate stable asthma and that bronchial epithelium damage and airway responsiveness may be partially associated with the eosinophilic inflammatory reaction [8]. There is also much evidence that bronchial asthma is characterized by chronic recruitment of eosinophils to the airways, and eosinophils play an important role in bronchial epithelial damage in asthma by releasing cationic proteins [9–11]. Allergen exposure in atopic asthmatic patients is associated with recruitment and activation of eosinophils in the airways.…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils release toxic products, including the eosinophil cationic protein (ECP), which damage bronchial structures, and increase bronchial hyperresponsiveness once they are activated [12]. Serum ECP is thought to be a useful marker of eosinophilic inflammation in bronchial asthma [9–11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the cut-off value of sputum eosinophil count (Ն5%) used in this study also has been verified by another group using 41 asthmatic patients and 27 nonasthmatic subjects. 12 We conclude that allergen-specific IgE antibodies in induced sputum from atopic asthmatics are associated with sputum eosinophilia. This result suggests that IgE-dependent mechanisms are involved in eosinophilic inflammation of the airway in atopic asthmatics.…”
Section: Discussionmentioning
confidence: 70%
“…We chose this cutoff value on the basis of our previous study 11 and the validation of sensitivity and specificity by another group. 12 …”
Section: Sputum Processingmentioning
confidence: 99%
“…However, a marker of airway inflammation does not necessarily correlate with asthma severity. For example, recent studies have shown that there is no correlation between sputum eosinophilia, a hallmark of airway inflammation in asthma, and asthma severity (10), and between sputum ECP levels and pulmonary function (11). We speculate that factors other than airway inflammation, such as airway remodeling, might also contribute to asthma symptoms and airflow limitation.…”
Section: Discussionmentioning
confidence: 94%